#TITLE_ALTERNATIVE# - Sihombing, Kawan
Abstract : Bauxite is a highly priced mineral because it contains as a mayor constituents aluminium, iron and silicone and as minor constituent titanium. Titanium is used to produce alloys which are corrosive, heat and high pressure resistant. The determination of titanium in bauxite used the spectrophotometric H2O2 method and Diantipyrylmethane (DAPH) method. The H2O2 method was based on .the formation of a - yellow complex, which maximum absorption at 400 nm with a molar extinction coefficient 740 L mol-1 cm-1. The DAPM method was based on the formation of a yellow complex with maximum absorption at 390 nn and. a molar extinction coefficient 15,000 L mol-1 cm-l. The result of the research indicatedthat the concentration range of TiO2 for the H2O2 method was 23 - 90 ppm with a sensitivity of 0.49 ppm. The concentration range for the DAPH method was 1.2 - 4.9 ppm with a sensitivity of 0.027 ppm. By using the appropriate statistical method, it was found that the standard deviation (S) for the HzOz method (1.81) was higher than for the DAPH method (0.73). The percentage recovery of TiO2 using the HzOz method was 93.40 + 1.52, lower than for the DAPH method 97.02 + 0.62. It may be concluded that for the determination of Ti in bauxite the spectrophotometric DAPH method is better than the H202 method.